A decade of contributions to understanding and ameliorating attention deficit-hyperactivity disorder. Issue 1 (December 2016) - Killeen, Peter
Abstract Background It has been 10 years since Terje Sagvolden foundedBehavioral and Brain Functions. Body After setting the context, this paper reviews some of the contributions of articles in the journal to the literature on ADHD over that decade. Those articles provide a cross section of some of the most important ongoing themes in ADHD research. Conclusion Terje's faith in the new journal was well founded. It has survived the first threat of new journals, crib death, because of the continuing quality and relevance of the articles it carries. It has a diversified portfolio of similar research in many other fields of related interest.